Power quality analysis of the grid-connected PV system using microinverter - Ngo Xuan Cuong; Do Nhu Y (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
At present, small-scale grid-connected PV system is increasingly developed and used in many households. These small-scale PV system are often connected to grid using microinverter, because its advantages are low maintenance investment costs, ease of installation and operation and do not cause environmental pollution. The content of the article focuses on power quality analysis of the non-stored grid-connected PV system using microinverter. The research method in the paper is based on experiments on models and laboratory measurements. The analytical results will assess the power quality of grid-connected PV system using microinverter, thereby managers and operators to take measures to improve the power quality of the electrical system with grid-connected PV system.